SYNTHESIS OF MULTI-CHANNEL SYSTEM OF ELECTRIC POWER IN THE UNFAVORABLE SITUATIONS - Казак, В.М.; Новачук, Л.В. (Proceedings of National Aviation University (archive), 2012)
Analysis of modern electric power of light signaling complex of aerodrome is conducted. Synthesis of parametric identification of multi-channel systems of electric power in unfavorable situations is conducted and variable does not change in time interval of observation, is a sequence of independent at each step of unfavorable variables, is a Markov chain.